Degradation of phenols in olive oil mill wastewater by biological, enzymatic, and photo-Fenton oxidation - Justino, Celine (2020)
Background, aim, and scope Olive oil mill wastewater (OOMW) environmental impacts minimization have been attempted by developing more effective processes, but no chemical or biological treatments were found to be totally effective to mitigate their impact on receiving systems. This work is the first that reports simultaneously the efficiency of three different approaches: biological treatment by two fungal species (Trametes versicolor or Pleurotus sajor caju), enzymatic treatment by laccase, and chemical treatment by photo-Fenton oxidation on phenols removal. Materials and methods Those treatments were performed on OOMW with or without phenol supplement (p-coumaric, vanillin, guaiacol, vanillic acid, or tyrosol). OOMW samples resulted from treatments were extracted for phenols using liquid–liquid extraction and analyzed by gas chromatography coupled to mass spectrometry. Results Treatment with T. versicolor or P. sajor caju were able to remove between 22% and 74% and between 8% and 76% of phenols, respectively. Treatment by laccase was able to reduce 4% to 70% of phenols whereas treatment by photo-Fenton oxidation was responsible for 100% phenols reduction. Discussion Range of phenol degradation was equivalent between T. versicolor, P. sajor caju and laccase for p-coumaric, guaiacol, caffeic acid, and tyrosol in supplemented OOMW, which enhances this enzyme role in the biological treatment promoted by these two species. Conclusions Phenols were removed more efficiently by photo-Fenton treatment than by biological or enzymatic treatments. Recommendations and perspectives Use of fungi, laccase, or photo-Fenton presents great potential for removing phenols from OOMW. This should be further assessed by increasing the application scale and the reactor configurations effect on the performance, besides a toxicity evaluation of treated wastewater in comparison to raw wastewater.